2019
DOI: 10.1177/1469066718822643
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of the vibronic structure of phenetole in its first excited state and ionic ground state

Abstract: The vibronic structure of the first electronically excited state S 1 and ionic ground state D 0 of phenetole has been investigated by means of resonance enhanced multi photon ionization (REMPI) and mass analyzed threshold ionization (MATI) spectroscopy. The vibronic levels were assigned with the aid of quantum chemical calculations at the (TD)DFT level of theory and a multidimensional Franck-Condon approach. The S 1 excitation energy of phenetole has been determined to be 36370 AE 4 cm À1 (4.5093 AE 0.0005 eV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Thus, simple FC overlap approximations based on harmonic vibration are not adequate for estimating the intensities of some vibronic bands. The simulated vibronic spectra of anisole, phenetole, trans -2-fluorostyrene, and p -chloroanisole have been reported in previous studies. ,,, …”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Thus, simple FC overlap approximations based on harmonic vibration are not adequate for estimating the intensities of some vibronic bands. The simulated vibronic spectra of anisole, phenetole, trans -2-fluorostyrene, and p -chloroanisole have been reported in previous studies. ,,, …”
Section: Resultsmentioning
confidence: 61%
“…The simulated vibronic spectra of anisole, phenetole, trans-2-fluorostyrene, and p-chloroanisole have been reported in previous studies. 32,33,35,36 The 1C-R2PI experiments revealed that the vibronic transitions of 2,4-difluoroanisole may involve ring-substituent and intramolecular through-space substituent−substituent interactions of the two F atoms and the OCH 3 group as well as ring deformation vibrations. Table 1 lists the observed vibronic bands of 2,4-difluoroanisole (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, Bloino et al and Barone et al successfully simulated vibrationally resolved electronic spectra of benzene derivatives by using the Gaussian package. Recently, Helle et al used the quantum chemical approach to obtain reliable results in multidimensional Franck–Condon simulations for detailed analysis of the vibronic and cation spectra of phenetole. We employed the procedure provided by the Gaussian 16 package for spectral simulation, which involves calculations of electronic spectra and frequency calculations for both initial and final states.…”
Section: Resultsmentioning
confidence: 99%